"A fountain of the richest poetry": Anna Jameson, Elizabeth Eastlake and the Rediscovery of Early Christian Art. (3rd April 2017) - Palmer, Caroline
Abstract : This article explores the relationship between women, art and religion in early nineteenth-century Britain by focusing on women's contributions to art criticism. It will argue that because women were seen as "naturally" skilled in the understanding of both art and religion, they were well placed to develop the increasing taste for early Christian art, which was rapidly acknowledged as an area of female expertise. Together with Maria Callcott (1785–1842), Anna Jameson (1794–1860) and Elizabeth Eastlake (1809–93) are now seen as key figures for the rise of female connoisseurship in this period, and both were central to the revival of interest in late medieval and early Renaissance – or so-called "Primitive" – art. I argue that the new insights they expressed arose from their shared engagement with German culture, which significantly influenced their approach to connoisseurship. Although the religious context lent their writing greater credibility, it was their linguistic expertise and awareness of art-historical developments in Germany that enabled them to make such an important contribution to this revolutionary shift in nineteenth-century taste.